Universal bionic interface reinforced composite solid electrolyte and preparation method and application thereof

The continuous ceramic nanofiber and natural polyphenol modified interface layer were prepared by electrospinning method to build an efficient bionic interface layer, which solved the problems of discontinuous ion transport and poor interfacial compatibility in composite solid electrolytes, and significantly improved lithium metal batteries electrochemical stability and safety.

CN119181846APending Publication Date: 2024-12-24DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411318656.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Uneven dispersion of inorganic fillers and poor organic-inorganic interface compatibility in composite solid electrolytes leads to discontinuous ion transmission paths and low interfacial ion transmission efficiency, limiting the electrochemical performance and safety of lithium metal batteries.

Method used

The three-dimensional continuous perovskite La0.56Li0.33TiO3 ceramic nanofibers were prepared as an inorganic framework by electrospinning. Combined with natural polyphenol-modified interface layer, the bionic interface layer was constructed through heat-induced polymerization to improve the interface ion transmission efficiency and conductance. Rate.

Benefits of technology

It significantly improves the ion conductivity and lithium ion migration number of the composite solid electrolyte, enhances the electrochemical stability and safety of lithium metal batteries, and can cyclize stably under high-rate charging and discharge conditions and show excellent safety and practicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181846A_ABST
    Figure CN119181846A_ABST
Patent Text Reader

Abstract

The invention provides a universal bionic interface reinforced composite solid electrolyte as well as a preparation method and application thereof, and belongs to the field of solid lithium metal batteries. Aiming at the problem of low ion transmission efficiency of an organic-inorganic interface in a traditional composite solid electrolyte, a polyphenol interface layer is controllably grown in situ between a ceramic nanofiber and a polyether matrix, and rich polar functional groups and carbonyl groups on polyphenol are used as an anion limiting cage and a lithium ion accelerator; therefore, a bionic interface lithium ion'transmission highway 'with ion selectivity is constructed, and the ion transmission efficiency of an organic-inorganic interface is greatly improved. The composite solid electrolyte prepared by the invention still has excellent electrochemical stability under high magnification, and an assembled soft package battery still shows extremely high safety stability under severe conditions of folding, cutting, puncturing and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium metal batteries, and in particular relates to a universal bionic interface enhanced composite solid electrolyte and a preparation method and application thereof. Background Art

[0002] Driven by the growing demand for sustainable energy, portable electronic devices and electric vehicles, it is urgent to develop the next generation of energy storage technology with high energy density. The energy density of traditional lithium-ion batteries is approaching its limit and cannot meet the needs of advanced energy storage devices. Lithium metal batteries use lithium metal with high theoretical specific capacity (3860mAh g -1 ) is known as the negative electrode and is considered a powerful alternative to lithium-ion batteries. However, the practical application of lithium metal batteries is still limited by safety issues such as short circuit, thermal runaway and even explosion caused by traditional flammable electrolytes. Solid electrolytes contain no or little liquid and are expected to use their own high mechanical strength to inhibit the growth of lithium dendrites. They are considered to be an effective strategy to solve the safety issues of liquid lithium metal batteries.

[0003] In the existing solid electrolyte system, composite solid electrolytes have the advantages of both polymer solid electrolytes and inorganic solid electrolytes, and are expected to achieve good interface compatibility with electrodes and high ionic conductivity at the same time. They are considered to be ideal materials for developing a new generation of high-performance solid electrolytes. However, the electrochemical performance of composite solid electrolytes is still limited by the problem that inorganic fillers are unevenly dispersed and easily agglomerated, resulting in discontinuous ion transmission paths, and poor compatibility of organic-inorganic interfaces, resulting in low interface ion transmission efficiency. Therefore, designing and constructing a composite solid electrolyte structure with a continuous lithium ion conduction path and improving the organic-inorganic interface ion transmission efficiency, further increasing the ionic conductivity of the composite solid electrolyte, improving the cycle stability of the battery, and thus accelerating the commercial development process of the composite solid electrolyte are key scientific issues that need to be solved by technicians in this field. Summary of the invention

[0004] In view of the problem in the prior art that discontinuous ion transmission of composite solid electrolytes and low interface ion transmission efficiency lead to poor cycle performance of solid-state lithium metal batteries, the purpose of the present invention is to provide a universal bionic interface enhanced composite solid electrolyte to improve the electrochemical stability of lithium metal batteries.

[0005] Another object of the present invention is to provide a method for preparing a universal bionic interface-enhanced composite solid electrolyte, which improves the interface ion transfer efficiency by constructing a bionic ion selective interface layer at the interface between the organic matrix and the inorganic filler, so that the prepared composite solid electrolyte has high ionic conductivity and lithium ion migration number, thereby ensuring the electrochemical stability of lithium metal batteries under high-rate charge and discharge.

[0006] Another object of the present invention is to provide a solid-state soft-pack battery application of the composite solid electrolyte to demonstrate the extremely high safety stability and potential commercial prospects of the composite solid electrolyte.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] A universal bionic interface enhanced composite solid electrolyte is provided. A bionic interface layer is controllably constructed on the surface of an inorganic ceramic skeleton material, and a polyether-based precursor solution is added dropwise to initiate thermal polymerization to obtain a composite solid electrolyte.

[0009] Preferably, the inorganic ceramic skeleton material of the present invention is a perovskite-type La 0.56 Li 0.33 TiO3 ceramic nanofibers.

[0010] Preferably, the bionic interface layer of the present invention is natural polyphenol, which has a fast lithium ion transmission channel and exhibits efficient ion selectivity that mimics the function of cell membranes.

[0011] Preferably, the natural polyphenol biomimetic interface layer of the present invention is at least one of dopamine, tannic acid and gallic acid.

[0012] Preferably, the polyether-based precursor solution of the present invention is copolymerized by polyethylene glycol methyl ether acrylate and glycidyl methacrylate, and contains 20% by mass of lithium bistrifluoromethanesulfonyl imide.

[0013] A method for preparing a universal bionic interface enhanced composite solid electrolyte comprises the following steps:

[0014] Step 1: Preparation of inorganic ceramic skeleton material by electrospinning;

[0015] Step 2: Natural polyphenols modify inorganic ceramic framework materials;

[0016] Step 3: Prepare a composite solid electrolyte by thermally initiating polymerization of a polyether-based precursor solution.

[0017] Preferably, the polyphenol modification polymerization time in step 2 of the present invention is 24 hours, and the polyphenol concentration is 0.5 mg / mL to 4 mg / mL.

[0018] Preferably, the thermally initiated polymerization procedure in step 3 of the present invention is: polymerization at 65° C. for 2 h, heating to 100° C. and continuing the reaction for 1 h.

[0019] An application of a universal bionic interface enhanced composite solid electrolyte, wherein the solid electrolyte is applied to a solid soft-pack battery.

[0020] The beneficial effects of the present invention are:

[0021] (1) In view of the problems of uneven dispersion and easy agglomeration of inorganic fillers in composite solid electrolytes in the prior art, which cause discontinuous ion transmission paths, the present invention adopts an electrospinning method to prepare three-dimensional continuous LLTO ceramic nanofibers as an inorganic skeleton structure, avoiding the agglomeration problem of high-content inorganic fillers. In addition, nanofibers with an aspect ratio and overlapping with each other can form a three-dimensional continuous ion conduction network in the composite solid electrolyte, thereby increasing the continuous transmission channels of lithium ions in the composite solid electrolyte, which is beneficial to improving the ionic conductivity of the composite solid electrolyte.

[0022] (2) The strategy of biomimetic interface enhancement composite solid electrolyte described in the present invention has extremely high stability and versatility. Compared with the interface modification means of composite solid electrolyte in the prior art, the interface modification method provided by the present invention can simultaneously form a strong chemical interaction with the polyether matrix and the inorganic ceramic nanofiber, thereby greatly improving the interface compatibility between the two; in addition, the abundant polar functional groups on the polyphenol interface layer can form hydrogen bonds with the anions in the lithium salt to restrict the movement of the anions, and the carbonyl group as a carrier of lithium ion transmission accelerates the transmission of lithium ions on the interface, thereby constructing a biomimetic "highway" for selective transmission of lithium ions on the organic-inorganic interface, significantly improving the ion transmission efficiency at the organic-inorganic interface in the composite solid electrolyte. In addition, the biomimetic interface modification strategy has extremely high versatility, and the interface material can be selected from polyphenols such as dopamine, tannic acid and gallic acid, etc., and can also be applied to construct the polyphenol interface modification layer on the surface of various inorganic fillers, thereby broadening the scope of application of the method.

[0023] (3) The composite solid electrolyte prepared by the present invention can increase the continuous lithium ion transmission path and construct a fast lithium ion transmission channel, thereby having a higher room temperature ion conductivity and lithium ion migration number. The button battery assembled using the composite solid electrolyte can stably cycle 1000 times under high current density charge and discharge conditions, and the assembled soft-pack battery can stably cycle 600 times and still maintain a high capacity retention rate of 82.85%, and can still stably light up the light strip under harsh test conditions such as folding, cutting, and puncture, showing excellent electrochemical stability and extremely high safety and practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on the provided drawings without creative work.

[0025] Figure 1are scanning electron microscope images of ceramic nanofiber membranes; (a) is a scanning electron microscope image of an inorganic skeleton LLTO ceramic nanofiber membrane, (b), (c), and (d) are scanning electron microscope images of LLTO ceramic nanofiber membranes modified with dopamine at different concentrations of 0.5 mg / mL, 2 mg / mL, and 4 mg / mL, and the illustrations correspond to the polydopamine-modified inorganic ceramic nanofiber membranes in Examples 1, 2, and 3, respectively.

[0026] Figure 2 The following are photos showing the composite solid electrolyte in different states prepared in Example 2; (a) is a photo showing the flexibility of the composite solid electrolyte provided by the present invention; and (b) is a photo showing the adhesion of the composite solid electrolyte provided by the present invention.

[0027] Figure 3 These are photos of actual applications of solid-state soft-pack batteries, among which (a) is a photo of an actual application of a solid-state soft-pack battery assembled with a composite solid electrolyte provided by the present invention; (b) is a photo of a cycle test of a soft-pack battery; (c), (d), (e), and (f) are photos of actual safety demonstrations of soft-pack batteries. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Any supplement, equivalent replacement or modification made within the technical scope of the present invention should be included in the protection scope of the present invention.

[0029] A universal bionic interface enhanced composite solid electrolyte comprises the following raw materials: an inorganic skeleton material, a polyphenol interface layer, a polyether-based polymer and a lithium salt, wherein the mass fraction of the lithium salt is 20% of the mass of the polyether-based polymer.

[0030] In a preferred embodiment of the present invention, the inorganic skeleton material is a perovskite-type lanthanum lithium titanate La 0.56 Li 0.33 TiO3 (LLTO) ceramic nanofibers.

[0031] In a preferred embodiment of the present invention, the polyphenol interface layer is one or more of dopamine, tannic acid, and gallic acid, preferably dopamine.

[0032] In a preferred embodiment of the present invention, the polyether-based polymer is copolymerized by polyethylene glycol methyl ether acrylate (PEGMA) and glycidyl methacrylate (GMA).

[0033] In a preferred embodiment of the present invention, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0034] The present invention also provides a method for preparing a universal bionic interface enhanced composite solid electrolyte, comprising:

[0035] Step 1: Preparation of LLTO nanofibers: LLTO electrospinning solution is prepared according to a certain chemical equivalent, wherein the solvent is N,N-dimethylformamide (DMF) and acetic acid, and polyvinylpyrrolidone (PVP) is used as a spinning aid. LLTO nanofibers are prepared by electrospinning combined with high-temperature calcination process.

[0036] Step 2: Preparation of polyphenol-modified LLTO nanofibers: The LLTO nanofibers are immersed in a polyphenol aqueous solution, then fully washed with ultrapure water, and finally placed in a blast oven to thoroughly dry the water to obtain polyphenol-modified LLTO nanofibers.

[0037] Step 3: Preparation of composite solid electrolyte: PEGMA, GMA, lithium salt and thermal initiator are fully stirred to uniformly prepare a polymer precursor solution, which is then added dropwise to the above-mentioned polyphenol-modified LLTO nanofiber membrane to obtain the final composite solid electrolyte after thermal initiation polymerization.

[0038] The polyphenol aqueous solution is obtained by dissolving polyphenol in tris buffer.

[0039] The concentration of the polyphenol aqueous solution is 0.5-4 mg / mL, preferably 2 mg / mL.

[0040] The soaking time is 12 to 24 hours, preferably 24 hours.

[0041] The thermal polymerization procedure is to polymerize at 65° C. for 2 h, then raise the temperature to 100° C. and continue the reaction for 1 h.

[0042] The universal bionic interface enhanced composite solid electrolyte of the present invention is applied as a high-performance solid-state soft-pack battery.

[0043] The embodiment of the invention discloses a preparation method of a universal bionic interface enhanced composite solid electrolyte and application of the same in a solid soft-pack battery.

[0044] Example 1

[0045] A method for preparing a universal bionic interface enhanced composite solid electrolyte comprises the following steps:

[0046] (1) Preparation of LLTO ceramic nanofibers: Take a 20 mL glass bottle and record it as bottle 1. First, add 8 mL of DMF to bottle 1, and then add 1 g of PVP and stir it thoroughly. After PVP is completely dissolved, lithium nitrate, lanthanum nitrate hexahydrate, and tetrabutyl titanate are added to bottle 1 according to a fixed molar ratio. Finally, 2 g of acetic acid is added to prevent the hydrolysis of tetrabutyl titanate. The above mixed solution is stirred overnight to complete the preparation of LLTO electrospinning solution.

[0047] The prepared spinning solution was placed in a 10 mL needle tube, which was installed and fixed in the electrospinning machine for spinning. The electrospinning parameters were specifically set as follows: positive high voltage 15 kV, negative high voltage 0.8 kV, receiving roller speed 60 r / min, injection speed 0.08 mm / min, and needle distance 20 cm from the receiving roller. It should be noted that the ambient temperature was maintained at 26 ° C and the ambient humidity was 35% during spinning.

[0048] Finally, the successfully prepared LLTO ceramic fiber precursor is placed in a tubular furnace and sintered at high temperature in a specific segmented temperature increase program to obtain the inorganic skeleton LLTO ceramic nanofiber required in the present invention.

[0049] (2) Preparation of polyphenol-modified LLTO ceramic nanofibers: 15 mL of tris solution was placed in a beaker, and 0.5 mg / mL of dopamine and polyethyleneimine were added thereto. After the solution was fully dissolved, the LLTO ceramic nanofiber membrane obtained in step (1) was placed in the above beaker, and the LLTO ceramic nanofiber membrane was slowly shaken in a shaker for 24 hours before being taken out. The membrane was rinsed with ultrapure water several times to ensure that the excess dopamine on the surface was removed, and finally placed in a forced air oven and dried overnight at 85°C to obtain a polydopamine-modified LLTO ceramic nanofiber membrane.

[0050] (3) Preparation of composite solid electrolyte: Take a 20mL glass bottle and record it as bottle 2, add PEGMA and GMA monomer solution, wherein the mass ratio of PEGMA and GMA is 2:1. Then add azobisisobutyronitrile thermal initiator, the initiator content is 1% of the monomer mass, stir and mix evenly, then transfer bottle 2 to a glove box, add lithium salt LiTFSI with a mass fraction of 20% of the monomer mass, stir and dissolve the lithium salt to obtain a polymer precursor solution. Take 60uL of the polymer precursor solution, add it dropwise to the polydopamine-modified LLTO ceramic nanofiber membrane obtained in the above step (2), spread it evenly and let it stand for half an hour until the fiber membrane is fully infiltrated, then place it on a hot plate and heat it at 65°C for 2h to polymerize, then raise the temperature to 100°C and continue the reaction for 1h, and the final biomimetic interface strategy enhanced composite solid electrolyte can be obtained.

[0051] Assembly of solid-state lithium metal batteries: According to the assembly method of button batteries, take out the 2025 type battery shell, place the negative electrode shell at the bottom, followed by the shrapnel, gasket, lithium negative electrode, composite solid electrolyte, positive electrode, and finally cover the positive electrode shell and use a packaging machine to package the assembled battery to complete the preparation of the button battery.

[0052] Example 2

[0053] A method for preparing a universal biomimetic interface enhanced composite solid electrolyte, except that the dopamine concentration in step (2) is changed to 2 mg / mL, the other conditions are the same as in Example 1. In addition, the assembly of a solid soft-pack battery is also carried out as follows:

[0054] Assembly of solid-state soft-pack batteries: Weld the tabs to the aluminum foil on the positive electrode sheet and the copper foil respectively, roll the lithium foil tightly on the copper foil as the negative electrode, and assemble the negative electrode, composite solid electrolyte, and positive electrode in the order of assembly. After the assembly is completed, place them in an aluminum-plastic film and perform the packaging process on a sealing machine in the glove box to complete the preparation of the solid-state soft-pack battery.

[0055] Figure 2 The following are photos showing the composite solid electrolyte in different states prepared in Example 2; (a) is a photo showing the flexibility of the composite solid electrolyte provided by the present invention; and (b) is a photo showing the adhesion of the composite solid electrolyte provided by the present invention.

[0056] Example 3

[0057] A method for preparing a universal bionic interface enhanced composite solid electrolyte is disclosed. Except that the dopamine concentration in step (2) is changed to 4 mg / mL, other conditions are the same as those in Example 1 to obtain a corresponding bionic interface enhanced composite solid electrolyte.

[0058] Figure 1 The SEM images of ceramic nanofiber membranes; (a) is a SEM image of an inorganic skeleton LLTO ceramic nanofiber membrane. (b), (c), and (d) are SEM images of LLTO ceramic nanofiber membranes modified with dopamine at different concentrations of 0.5 mg / mL, 2 mg / mL, and 4 mg / mL, where the illustrations correspond to the polydopamine-modified inorganic ceramic nanofiber membranes in Examples 1, 2, and 3, respectively.

[0059] Example 4

[0060] The type of polyphenol in step (2) of Example 1 is changed, dopamine is replaced by tannic acid, the growth concentration of tannic acid is the same as that in step (2) of Example 2, and other conditions are the same as those in Example 1, to obtain the corresponding bionic interface enhanced composite solid electrolyte.

[0061] Example 5

[0062] The type of polyphenol in step (2) of Example 1 is changed, dopamine is replaced by gallic acid, the growth concentration of gallic acid is the same as that in step (2) of Example 2, and other conditions are the same as those in Example 1, to obtain the corresponding bionic interface enhanced composite solid electrolyte.

[0063] Comparative Example 1

[0064] The step (2) in Example 1 was not performed in the composite solid electrolyte, and the polymerization procedure was changed, that is, in step (3), polymerization was only performed at 65° C. for 2 h, and the other conditions were the same as in Example 1, to obtain the corresponding composite solid electrolyte.

[0065] Performance Test:

[0066] Test Example 1

[0067] Ionic conductivity test: The composite solid electrolytes prepared in Examples 1 to 5 and Comparative Example 1 were punched into discs with a diameter of 16 mm and placed between two steel sheets. AC impedance spectroscopy was tested at 25°C in the frequency range of 0.1 Hz to 100 kHz. The room temperature ionic conductivity of the composite solid electrolyte was calculated based on the measured composite solid electrolyte impedance and the formula. The calculation formula for ionic conductivity is as follows: σ = L / RS, where L is the thickness of the composite solid electrolyte (cm), R is the ohmic impedance (Ω) obtained from the test, and S is the contact area between the composite solid electrolyte and the steel sheet (cm 2 ), and the calculation results are shown in Table 1.

[0068] Test Example 2

[0069] Lithium ion migration number test: The composite solid electrolytes prepared in Examples 1 to 5 and Comparative Example 1 were punched into discs with a diameter of 16 mm and assembled into Li||Li symmetrical batteries. The AC impedance spectrum of the battery before polarization was tested using an electrochemical workstation to obtain the impedance value before DC polarization; then the current-time curve was measured, the test time was 10000 s, and the polarization voltage was set to 10 mV; finally, the AC impedance spectrum of the battery after DC polarization was measured again to obtain the impedance value after polarization. The lithium ion migration number calculation formula is t Li + =I s (ΔV-I0R0) / I0(ΔV-I s R s ), where I0, I s are the initial current and steady-state current before and after polarization, R0 and R s are the battery impedance values ​​before and after polarization, and ΔV is the polarization voltage. The calculation results are shown in Table 1.

[0070] Table 1 shows the room temperature ionic conductivity and lithium ion migration number calculated for Examples 1 to 5 and Comparative Example 1.

[0071] Group Name <![CDATA[Ionic conductivity (S cm -1 )]]> Lithium ion migration number Example 1 <![CDATA[2.91×10 -5 ]]> 0.57 Example 2 <![CDATA[3.57×10 -5 ]]> 0.64 Example 3 <![CDATA[2.23×10 -5 ]]> 0.68 Example 4 <![CDATA[2.79×10 -5 ]]> 0.54 Example 5 <![CDATA[2.61×10 -5 ]]> 0.62 Comparative Example 1 <![CDATA[1.17×10 -5 ]]> 0.44

[0072] From the data in Table 1, it can be seen that the composite solid electrolyte modified by polyphenol has a faster interface ion transport channel, which makes its room temperature ion conductivity 2 times higher than that of the unmodified composite solid electrolyte, and the lithium ion migration number is significantly improved. Moreover, for interface layers of different thicknesses and different compositions, consistent results are shown, which reflects the versatility of the biomimetic polyphenol interface modification strategy.

[0073] Test Example 3

[0074] Battery performance test: The composite solid electrolyte prepared in Examples 1 to 3 and Comparative Example 1 was punched into discs with a diameter of 16 mm and assembled into a Li|LiFePO4 full battery. The cyclic charge and discharge test was performed at 60°C with a rate of 1C, and the number of cycles was 600. The initial discharge specific capacity of each battery, as well as the discharge specific capacity after 600 cycles and the average coulombic efficiency (coulombic efficiency = discharge specific capacity / charge specific capacity × 100%) were recorded. The capacity retention rate of each battery was obtained according to the formula: Capacity retention rate = (discharge specific capacity after cycle / initial discharge specific capacity) × 100%, and all the results are shown in Table 2.

[0075] Table 2 shows the electrochemical performance test results of the batteries of Examples 1 to 5 and Comparative Example 1 under 1C rate test conditions.

[0076]

[0077] From the data in Table 2, it can be seen that the electrochemical performance of the composite solid electrolyte modified by dopamine interface is significantly improved, and the coulombic efficiency and capacity retention rate are much higher than those of the solid electrolyte without interface modification. This result shows that the construction of a fast interface ion transport channel accelerates the transmission kinetics of lithium ions on the interface, significantly improves the ionic conductivity of the composite solid electrolyte, and thus improves the cycle stability of the battery.

[0078] Test Example 4

[0079] In order to further verify the versatility of the composite solid electrolyte modified by the bionic interface strategy, a battery test was conducted: the composite solid electrolyte prepared in Examples 2, 4, 5 and Comparative Example 1 was punched into discs with a diameter of 16 mm and assembled into a Li|LiFePO4 full battery, and a cyclic charge and discharge test was performed at 60°C at a rate of 5C, with a cycle number of 1000. The initial discharge specific capacity of each battery, as well as the discharge specific capacity after 1000 cycles and the average coulombic efficiency (coulombic efficiency = discharge specific capacity / charge specific capacity × 100%) were recorded. The capacity retention rate of each battery was obtained according to the formula: Capacity retention rate = (discharge specific capacity after cycle / initial discharge specific capacity) × 100%, and all results are shown in Table 3.

[0080] Table 3 shows the electrochemical performance test results of the batteries of Examples 2, 4, 5 and Comparative Example 1 under 5C rate test conditions.

[0081]

[0082] From the results in Table 3, it can be seen that the batteries assembled in Examples 2, 4, and 5 show more outstanding electrochemical performance under high-rate charge and discharge than the control samples. Under the 5C charge and discharge high-rate test conditions, the initial discharge specific capacity of the battery after interface modification is nearly twice that of the unmodified one. Moreover, after 1,000 cycles, the discharge specific capacity of the batteries assembled in Examples 2, 4, and 5 is still significantly higher than that of Comparative Example 1. Combined with the data in Table 1, it is shown that after interface modification in the composite solid electrolyte, the ion transport kinetics of the composite solid electrolyte will be accelerated, the ionic conductivity will be improved, and thus the electrochemical stability of the battery will be improved. These results further highlight the versatility of the preparation method of a bionic interface enhanced composite solid electrolyte provided by the present invention.

[0083] Application Examples

[0084] Application of solid-state soft-pack battery: The solid-state soft-pack battery prepared in Example 2 was applied and demonstrated to have a stable open circuit voltage of 3.4V and to stably light up the thermometer and hygrometer, demonstrating the practicality of the composite solid electrolyte described in the present invention. In addition, the soft-pack battery was subjected to folding, cutting and puncture experiments, and the leakage and flammability of traditional liquid batteries did not occur, and the light strip could still be stably lit. Figure 3 As shown, (a) is a photo of a solid soft-pack battery assembled with a composite solid electrolyte provided by the present invention; (b) is a photo of a cycle test of a soft-pack battery; (c), (d), (e), and (f) are photos of the safety of soft-pack batteries. It shows that the composite solid electrolyte provided by the present invention has extremely high safety stability and potential application value.

Claims

1. A universal bionic interface enhanced composite solid electrolyte, characterized by: A bionic interface layer is controllably constructed on the surface of an inorganic ceramic skeleton material, and a polyether-based precursor solution is added dropwise to initiate thermal polymerization to obtain a composite solid electrolyte.

2. A universal bionic interface enhanced composite solid electrolyte according to claim 1, characterized in that: The inorganic ceramic skeleton material is a perovskite-type La 0.56 Li 0.33 TiO3 ceramic nanofibers.

3. A universal bionic interface enhanced composite solid electrolyte according to claim 1, characterized in that: The bionic interface layer is a natural polyphenol with a fast lithium ion transmission channel, showing efficient ion selectivity that mimics the function of cell membranes.

4. A universal bionic interface enhanced composite solid electrolyte according to claim 3, characterized in that: The natural polyphenol bionic interface layer is at least one of dopamine, tannic acid and gallic acid.

5. The universal bionic interface enhanced composite solid electrolyte according to claim 1, characterized in that: The polyether-based precursor solution is copolymerized by polyethylene glycol methyl ether acrylate and glycidyl methacrylate, and contains 20% by mass of lithium bistrifluoromethanesulfonyl imide.

6. A method for preparing the universal bionic interface enhanced composite solid electrolyte according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Preparation of inorganic ceramic skeleton material by electrospinning; Step 2: Natural polyphenols modify inorganic ceramic framework materials; Step 3: Prepare a composite solid electrolyte by thermally initiating polymerization of a polyether-based precursor solution.

7. A method for preparing a universal bionic interface enhanced composite solid electrolyte according to claim 6, characterized in that: The polyphenol modification polymerization time in step 2 is 24 hours, and the polyphenol concentration is 0.5 mg / mL to 4 mg / mL.

8. A method for preparing a universal bionic interface enhanced composite solid electrolyte according to claim 6, characterized in that: The thermal polymerization procedure in step 3 is: polymerization at 65°C for 2 hours, heating to 100°C and continuing the reaction for 1 hour.

9. An application of the universal bionic interface enhanced composite solid electrolyte according to any one of claims 1 to 5, characterized in that: The solid electrolyte is applied to solid-state soft-pack batteries.